ESTIMATION OF RESIDUAL SOLVENTS IN NETUPITANT API BY HEADSPACE GAS CHROMATOGRAPHY - GODE, SUNNY GRACE; LAKSHMI G., VIJAYA (International Journal of Pharmacy and Pharmaceutical Sciences, 2021)
Objective: Residual solvents are undesirable components present in Active Pharmaceutical Ingredients (API), excipients, or drug products. To meet the specific quality-based requirements, the presence of these solvents in pharmaceutical products should be monitored to ensure their safety. The main objective of this work is to develop a new method for the determination of residual solvents in netupitant API by an HS-GC method with an FID detector. Methods: An automated headspace GC method has been developed and validated for the estimation of the residual solvents-N-methyl pyrrolidine, xylene, toluene, and N, N Dimethylacetamide in netupitant API. The samples were dissolved in dimethyl sulfoxide and the equilibrium headspace gas was formed at 80 ᵒC, which was analyzed using a DB-624 column (30m*0.53 mm, 3.00 µm) with an injector and detector temperature set at 160 ᵒC and 230 ᵒC, respectively. The initial oven temperature was set at 60 ᵒC for 5 min and programmed at a rate of 10 ᵒC/min to the final temperature of 150 ᵒC, with a hold time of 5 min by maintaining the flow rate of 4.0 ml/min with a split ratio of 1:10, and total run time of 20 min. Nitrogen was used as carrier gas. The method developed was validated as per International Conference for Harmonization (ICH) guidelines for repeatability, linearity, range, ruggedness, detection limit, quantification limit, and recovery studies. Results: The linearity range selected was 50-350µg/ml and the correlation coefficient(γ2) values for all the solvents were found to be>0.99; recovery studies values were in a range of 90-110% and %RSD values were also found to be not more than 10 for the solvents. Conclusion: A novel, accurate, sensitive, and simple method was described for estimating residual solvents in Netupitant API by Headspace Gas Chromatography (HS-GC) coupled with a Flame Ionization Detector (FID). Excellent results have been observed for all the validated parameters with good peak resolution and lesser retention times.